Integrating life skills into small-game courses within the context of positive youth development. - Nuriska Subekti; Agus Mulyadi; Endah Listyasari; Juhrodin Juhrodin (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
This study aims to obtain empirical evidence on the healthy development of adolescents in a small-sided game course by integrating life skills. A Matching-Only Pre-test Post-test Control Group Design utilizing a Quasi-Experimental Design methodology was applied as the research design. The study utilized a representative sample of fourth-semester students enrolled in the short game course. The sample consisted of three groups: Group A was the youth participating in the small-sided game course integrated with life skills (up to 24 individuals); Group B comprised the youth taking part in the small-sided game course without integrated life skills (up to 27 individuals); and a control group from another class (up to 25 individuals). The Life Skills Scale for Sport (LSSS) questionnaire instrument was employed in this research. Statistical analysis revealed that the t-count value of 5.295 is higher than the t-table value of 2.010. It indicates a significant difference between the groups or conditions compared in the analysis. The findings suggest that integrating life skills in the small-sided game course significantly impacts the measured outcomes. Further analysis and interpretation of the statistical results are required to understand the specific nature and magnitude of the observed differences. In conclusion, this study contributes to the understanding of promoting positive adolescent development by integrating life skills in a small-sided game course. The findings highlight the significance of incorporating life skills into sports education programs for fostering holistic growth among adolescents.Keywords: Positive youth development, small game learning, Life skills.